Comparative Study of Stress and Strain Analysis on a Hip End Effector for Orthopedic Surgical Applications Using Different Materials - Ganguly, Rohan (My University, 2025)
Robotic-assisted total hip arthroplasty (THA) has rapidly advanced as a transformative technology in orthopedic surgery. This innovative approach integrates navigation, minimally invasive techniques, and precise robotic arm control to enhance the accuracy of preoperative planning, implant selection, osteotomy, and artificial joint placement. The inherent accuracy and stability of robotic systems have led to their increasing adoption, particularly in hip and knee arthroplasty, and are recognized for improving implant positioning and reducing limb length discrepancies compared to conventional manual techniques. The precision offered by these systems in achieving planned acetabular positioning and restoring the center of hip rotation is well-documented. While initial clinical outcomes appear largely comparable to traditional methods, the long-term benefits, implant survivorship, time to revision surgery, and cost-effectiveness of robotic THA continue to be areas of active investigation and require further high-quality studies. A pivotal component underpinning the precision and efficacy of robotic THA is the surgical end effector. This instrument directly engages with bone and tissue during critical surgical phases, such as reaming, cutting, and implant impaction. The structural integrity, mechanical performance, and long-term durability of these end effectors are of paramount importance, directly influencing patient safety and the overall success of the surgical procedure. This thesis undertakes a comprehensive investigation into the stress, strain, and material analysis of a hip end effector specifically designed for orthopedic surgical applications within robotic-assisted platforms. This study focuses on the mechanical behavior of the hip end effector when fabricated from three distinct and commonly employed biocompatible materials known for their applications in surgical implants and instruments: 17-4 PH stainless steel, Cobalt alloys, and Titanium alloys. Through detailed computational modeling, specifically employing Finite Element Analysis (FEA), this research aims to meticulously analyze the stress and strain distributions within the end effector design for each chosen material. The analysis will simulate various realistic surgical loading conditions encountered during THA procedures, such as impaction forces, torsional loads, and bending moments, with specific attention to applied loads of 5000 N and 7500 N. The primary objective is to identify and characterize critical stress concentration points within the end effector structure. This involves determining von Mises stresses, and the corresponding elastic and plastic strains experienced by the device under these loads. iv Understanding these critical regions and the magnitudes of stress and strain will provide invaluable insights into the potential areas of mechanical weakness, susceptibility to plastic deformation, and susceptibility to fatigue crack initiation and propagation. This knowledge is crucial for predicting the fatigue life and potential failure modes of the end effector, which in turn will inform material selection, guide structural design optimizations, and enhance the overall reliability and safety of the instrument. The findings from this research are expected to contribute significantly to the ongoing development of more robust, durable, and reliable robotic surgical instruments, thereby playing a vital role in advancing the capabilities and widespread adoption of robotic-assisted arthroplasty, ultimately benefiting patient outcomes.
Keywords: Robotic-Assisted Total hip arthoplasty; Hip End Effector; Finite Element Analysis(FEA); Biocompatible Materials; Stress/Strain Analysis